Ferritin as a Dual-Purpose Biomarker: Unraveling its Role in Iron Storage and as a Surrogate for Tumor Burden in CML - Salih, Amjed Abbawe; Ali, Jassim Mohammed; Al Ghuraibawi, Zahraa A.G.; Abd, Muqdad Khamis; Jumaa, Azal Hamoody (Asian Pacific Journal of Cancer Biology, 2026)
Background: Hyperferritinemia observed in patients with chronic myeloid leukemia (CML) presents an interpretive challenge, as its underlying cause may be attributable to either iron overload or an inflammatory response associated with the tumor. Accurate identification of the primary driver is essential for precise clinical assessment. Objective: This investigation sought to elucidate the principal cause of elevated ferritin levels in patients with newly diagnosed chronic myeloid leukemia (CML) and to assess the diagnostic effectiveness and utility of the calculated Iron/Ferritin and TIBC/Ferritin ratios. Materials and Methods: This retrospective, cross-sectional study involved 90 adult patients with untreated chronic-phase CML. At diagnosis, serum ferritin, lactate dehydrogenase (LDH), iron levels, and total iron-binding capacity (TIBC) were measured. The relationships between ferritin, LDH, and iron parameters were examined using Spearman’s correlation and multiple linear regression, with ferritin log10-transformed. Patients were divided at the median LDH level, and the Mann-Whitney U test was used to compare the proposed ratios between groups with high and low disease burden. Results: The cohort demonstrated pronounced hyperferritinemia, with a median ferritin level of 339.5 μg/L, and elevated lactate dehydrogenase (LDH), with a median of 269.2 U/L. Concurrently, serum iron and total iron-binding capacity (TIBC) were markedly reduced. A moderate positive correlation was observed between ferritin and LDH (ρ=0.52, p<0.001), whereas the correlations with iron and TIBC were weak and not statistically significant. Regression analysis identified LDH as the only independent predictor of ferritin levels (β = 0.56, p < 0.001). Furthermore, the ratios of iron to ferritin and TIBC to ferritin were significantly lower in the high LDH group (median Iron/Ferritin: 0.038 vs. 0.068; median TIBC/Ferritin: 0.150 vs. 0.295; p<0.001 for both), indicating inflammation-driven alterations and suggesting an association with inflammation-driven iron metabolism changes. Conclusion: This investigation introduces a pragmatic and economical diagnostic methodology (the utilization of the Iron/Ferritin and TIBC/Ferritin ratios) that facilitates clinicians in precisely determining hyperferritinemia caused by tumor-associated inflammation in patients with newly diagnosed CML, thereby obviating the need for superfluous iron-related examinations. In this cohort of treatment-naïve CML patients, hyperferritinemia was primarily associated with tumor-related inflammation rather than iron overload. The Iron/Ferritin and TIBC/Ferritin ratios may serve as simple, cost-effective tools to suggest an inflammatory etiology, though further validation in prospective studies with ROC analysis is warranted.